Transforming Northern Nias’ Omo Hada Traditional House Into Product Packaging - Lintang Ratna Anindita; Remandhia Mulcki; Ester Griselia; Fadhilah Hanan Ramadhan; Sarah Leandra; Tyvania Rakhmasashi Soesilo (Universitas Indraprasta PGRI, 2022)
Omo Hada, a traditional house of the island of Nias, North Sumatra, is on the verge of extinction. The ability for locals to sustain their cultural heritage has weakened due to various factors. To remind, reintroduce, and reconnect Nias locals to their cultural heritage, the authors try to combine fundamental elements of the northern Nias Omo Hada traditional house with a modern object commonly found on a daily basis, which is product packaging. By using the ATUMICS method to transform this form of tradition, authors believe that the traditional essence in product packaging can be conveyed through visual graphics, while at the same time relifting the harmony of Indonesian culture and traditions. The implementation of traditional elements in the product packaging’s design is believed to evoke a connection with its local consumers